New intervention in mitral valve prolapse. Use of cold pressor test during echocardiography. Issue 5 (November 1980) - Pitcher, D; Tynan, M; Wainwright, R; Curry, P; Sowton, E
Abstract : A study was performed in 13 patients with idiopathic mitral valve prolapse and in 21 control subjects to assess the effect of the cold pressor test on systolic motion of the mitral valve. A significant increase in blood pressure occurred in 10 patients with mitral valve prolapse and in 19 controls after immersion of one hand in ice-cold water. M-mode echocardiographic recordings from the mitral valve were obtained in all patients before, during, and after the cold pressor test, together with simultaneous phonocardiograms in selected patients. Nine out of 10 patients with mitral valve prolapse and a hypertensive response to the cold stimulus showed a significant increase in the depth of mitral valve prolapse during the cold pressor test whereas in three patients with mitral valve prolapse and no hypertensive response the depth of mitral valve prolapse did not change during cold stimulation. Three patients with previously demonstrated mitral valve prolapse had equivocal resting echocardiograms but developed diagnostic evidence of mitral valve prolapse during the cold pressor test. No evidence of mitral valve prolapse was seen in any of the control subjects before, during or after the cold pressor test. In four patients with mitral valve prolapse and a hypertensive response to cold stimulation the systolic click was delayed by the cold pressor test, whereas the time of the systolic click remained constant in the three patients whose blood pressure did not increase. It is concluded that the cold pressor test provides a stimulus sufficient to delay the onset and increase the depth of mitral valve prolapse, thereby enhancing the diagnostic sensitivity of echocardiography in this condition.